Redescription of Pseudotropheus livingstonii and Pseudotropheus elegans from Lake Malaŵi, Africa - Stauffer, J.r. Jr.; Konings, A F.; Ryan, T.m. (Zootaxa, 2016)
Pseudotropheus livingstonii and P. elegans are two sand-dwelling cichlid species that belong to the so-called mbuna, a group of predominantly rock-dwelling haplochromines of Lake Malaŵi. The identity of these two species has confused taxonomists for almost a century until a recent rediscovery of representatives of P. elegans close to its type locality. New diagnoses for both species are provided.